2018
DOI: 10.29312/remexca.v0i9.1045
|View full text |Cite
|
Sign up to set email alerts
|

Revitalización de fincas cafetaleras por medio del turismo rural: caso del municipio Coatepec, Veracruz

Abstract: ResumenEl modelo económico neoliberal y la liberalización comercial del café trajo consigo rezagos en la actividad, desplazamiento de la producción interna que ocasionó el cierre de campos productivos poco competitivos en el mercado global y conflictos sociales como la pobreza y la migración. Ante esto, se impulsaron opciones como programas de bienestar social y empleo rural no agrícola (ERNA) entre ellos el turismo rural. La investigación se realizó en el municipio de Coatepec, Veracruz, productor de café y d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…Duarte argued that the development of rural tourism in Portugal should focus on the marketing and promotion of rural tourism [52]. Using coffee plantations as an example, Apodacagonzdlez et al suggested that coffee farms should be revitalised through the development of rural tourism with coffee experiences as a theme [53]. Roberta MacDonald, in a study based on the rural tourism industry in Canada, pointed out that the important factors and conditions for the development of rural tourism are policy support and characteristic rural culture [54].…”
Section: The Pathways Of Tourism Promoting Rural Revitalisationmentioning
confidence: 99%
“…Duarte argued that the development of rural tourism in Portugal should focus on the marketing and promotion of rural tourism [52]. Using coffee plantations as an example, Apodacagonzdlez et al suggested that coffee farms should be revitalised through the development of rural tourism with coffee experiences as a theme [53]. Roberta MacDonald, in a study based on the rural tourism industry in Canada, pointed out that the important factors and conditions for the development of rural tourism are policy support and characteristic rural culture [54].…”
Section: The Pathways Of Tourism Promoting Rural Revitalisationmentioning
confidence: 99%
“…Activities such as agrotourism contribute to the sustainable development of communities and, consequently, the conservation of these valued and profitable agroecosystems. However, the achievement of such outcomes mandates the active involvement of governmental and educational institutions in the undertaking, in addition to securing the enthusiastic participation of proprietors of natural and agricultural resources [42].…”
Section: Effects Of Land Cover and Land Use Changes On The Ncps Provi...mentioning
confidence: 99%
“…El turismo rural, y en especial el agroturismo, es considerado por las autoridades públicas y privadas como una estrategia para dinamizar el desarrollo de las zonas rurales por su capacidad de contribuir a la generación de ingresos adicionales a los productores agropecuarios (Blanco y Riveros, 2011 citado en Apodaca-González et al, 2014, p.1526.…”
Section: Figuraunclassified